Controlling carbon formation over Ni/CeO2 catalyst for dry reforming of CH4 by tuning Ni crystallite size and oxygen vacancies of the support. (March 2022) - da Fonseca, Renata O.; Ponseggi, Antonella R.; Rabelo-Neto, Raimundo C.; Simões, Rita C.C.; Mattos, Lisiane V.; Noronha, Fabio B.
Graphical abstract: Highlights: Effect of Ni crystallite size and oxygen mobility of the support on carbon formation. The amount of carbon formed during DRM achieved a maximum at around 20−30 nm. Carbon deposition was negligeable below 10 nm and above 100 nm. Coordinatively unsaturated sites (small Ni particle sizes) inhibit carbon formation. On very large Ni particles, the CH4 dissociation rate is so low that carbon reacts. Abstract: This work investigates the effect of Ni crystallite size and oxygen vacancies of the support on the formation of carbon over Ni/CeO2 catalysts for dry reforming of methane at 1073 K. A large crystallite size variation is achieved by using different Ni loading (5 and 10 wt%) and calcination temperatures (673, 873, 1073 and 1473 K). In situ XRD and XANES experiments reveal that the increase in calcination temperature increases the Ni crystallite size, whereas the amount of oxygen vacancies decreases. The amount of carbon formed during DRM increases as Ni crystallite size increases, achieving a maximum at around 20−30 nm and then, it continuously decreases. However, carbon deposition is negligeable below 10 nm and above 100 nm. For the catalysts with very large Ni crystallite sizes, the CH4 dissociation rate is likely so low that carbon species formed reacts and carbon accumulation does not take place. However, the oxygen vacancies of ceria do not contribute to the carbon removal from the Ni surface due to the low metal-support interface on these large Ni particles.